The Aura of Chips: Material Engagements and the Production of Everyday Religious Difference in British Asian Street Kitchens. (10th December 2019) - Zavos, John
Abstract: Religious difference is a significant index of social plurality in contemporary Britain. State discourses frequently project society as multi-faith, while simultaneously signaling religious others as a potential threat to social cohesion. Acknowledging the social power of these contrasting projections, this article analyses religious difference as an everyday feature of British urban pluralism. The article draws on Stuart Hall's recognition of processes of diaporic identification, shaped in the context of the pathologizing of racial identity as a fixed form of difference. It argues that an emphasis on identification, rather than identity, invokes a critique of agential approaches to everyday religious practices. Tim Ingold's proposition of material engagements as a "dance of animacy" provides an analytical tool to explore the production of religious difference beyond agency in this way. The article focuses on sensory engagements and diaspora food cultures in Sikh and Muslim street kitchen initiatives to explore these themes.